Effectiveness of Oxytocin Massage on Uterine Involution and Milk Production in Postpartum Mothers at the Gerakan Sayang Ibu dan Anak Clinic Nabire Papua - Umisisia Pigai; Tuty Yanuarti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Knowing the effectiveness of oxytocin massage on uterine involution and milk production in postpartum mothers Methods: Quasi-experimental with case-control research type. The sample in this study were all postpartum patients at the GSIA Nabire Clinic, Papua in March 2022 as many as 30 people were divided into 2 groups, 15 intervention groups, and 15 control groups (total sampling). Results:  Most postpartum mothers with normal uterine involution (80%) and milk production (50%). There is the effectiveness of massage on uterine involution and milk production in postpartum mothers with a p-value < 0.05 Conclusion: Massage effectiveness affects uterine involution and milk production in postpartum mothers. It is hoped that oxytocin massage will be used as a procedure at the GSIA Clinic so that postpartum mothers can provide exclusive breastfeeding to their children.